Therapeutic targeting potential of the protein lysine and arginine methyltransferases to reverse cancer chemoresistance - Micallef, Isaac; Fenech, Kimberly; Baron, Byron (Frontiers in Molecular Biosciences, 2024)
Cancer treatments have continued to improve tremendously over the past decade, but therapy resistance is still a common, major factor encountered by patients diagnosed with cancer. Chemoresistance arises due to various circumstances and among these causes, increasing evidence has shown that enzymes referred to as protein methyltransferases (PMTs) play a significant role in the development of chemoresistance in various cancers. These enzymes are responsible for the methylation of different amino acids, particularly lysine and arginine, via protein lysine methyltransferases (PKMTs) and protein arginine methyltransferases (PRMTs), respectively. Various PMTs have been identified to be dysregulated in the development of cancer and chemoresistance. Nonetheless, the functional role of these PMTs in the development of chemoresistance is poorly characterised. This advocates the need for innovative approaches and technologies suitable for better characterisation of these PMTs and their potential clinical inhibitors. In the case of a handful of PMTs, inhibitory small molecules which can function as anticancer drugs have been developed and have also entered clinical trials. Considering all this, PMTs have become a promising and valuable target in cancer chemoresistance related research. This review will give a small introduction on the different PKMTs and PRMTs families which are dysregulated in different cancers and the known proteins targeted by the respective enzymes. The focus will then shift towards PMTs known to be involved in chemoresistance development and the inhibitors developed against these, together with their mode of action. Lastly, the current obstacles and future perspectives of PMT inhibitors in cancer chemoresistance will be discussed.